DEVELOPING UNDERSTANDING OF INNOVATIVE STRATEGIES OF TEACHING SCIENCE THROUGH ACTION RESEARCH: A QUALITATIVE META-SYNTHESIS FROM PAKISTAN - HALAI, NELOFER (International journal of science and mathematics education, 2012)
ABSTRACT This study is a meta-synthesis of 20 action research studies undertaken in the classroom by teachers to develop their understanding of an innovative strategy for teaching science. The studies were undertaken as part of the requirements for their 2-year M.Ed. program from the Aga Khan University, Institute for Educational Development (AKU-IED), Pakistan. The teachers enrolled in the program are expected to conduct a small-scale study as part of their thesis requirement which counts for 16 credits or 25% of the program. Twenty studies from a total of 350 M.Ed. thesis were selected based on specific criteria that they (a) are qualitative action research studies, (b) are undertaken by teachers who themselves teach in the science classroom, and (c) use an innovative strategy for teaching science. The meta-synthesis shows that action research contributed to developing understanding in all three domains of teacher knowledge: pedagogical knowledge, subject matter knowledge, and pedagogical content knowledge. The teacher researchers developed an understanding of the theory and practice of the innovative strategy implemented and found that the transformation of their science content knowledge to “fit” the new ways of teaching was the most challenging and rewarding part of their research. They also found that the balance between innovative ways of teaching science and current methods of assessment was very hard to achieve and created a barrier to the acceptance of new methods of teaching.